Peach for the future: A specialty crop revisited - Manganaris, George A.; Minas, Ioannis S.; Cirilli, Marco; Torres, Rosario; Bassi, Daniele; Costa, Guglielmo (My University, 2022)
Peach is the most important temperate fruit crop worldwide in terms of production after apple. However, a descending trend has been registered over the recent years in several key producing peach countries, mainly due to the increased labor cost and the reduced revenue for the farmer. The present perspective review aims to shed light on the current trends on peach fruit production related to cultivar and rootstock breeding initiatives, appropriate training system selection and targeted integrated management of main diseases, most promptly Monilinia spp. Cultivar breeding programs should focus on the most relevant outcomes about the main drivers of consumer's acceptance. In the near future, a contribution from the breeding sector should be expected in the reduction of the trade-off between quality and yield, towards selection of elite cultivars with enhanced aroma (a pool of compounds still scarcely known), with appreciable nutritional properties and extended market life. Such cultivars need an appropriate rootstock and canopy architecture to facilitate efficient cropping systems. The training/cropping system selection is of equal importance with rootstock selection as it can also determine efficiency and potential for mechanization. A tendency for the future is that several semi- and dwarfing Prunus hybrid rootstocks aligned with the innovations on peach tree architecture will lead to higher planting densities, reduced tree height and thus enhanced peach production with reduced labor cost. With the aim to advance peach fruit production and consumption, there is an urgent need to dissect solutions to valorize on the market the exceptional peach diversity and flavor potential, already present in the varietal landscape. The development of sophisticated non-destructive tools that will allow in cost-effective manner to determine fruit quality and maturity stage is expected to facilitate consumer eating experience and storage requirements with minimum risk of chilling injury symptoms development. Lastly, the phytosanitary protocol of small-sized wall-grown plants would most likely be more effective and would require reduced quantities of pesticides while simultaneously responding to the needs of a market that is increasingly attentive to fruit healthiness and environment protection. Phytosanitary issues can be addressed by controlling diseases and/or by improving genetic resistance.
Keywords: Breeding; Chilling injury; Cultivar; Disease management; Dry matter content; Monilinia spp.; Non-destructive; Prunus persica; Rootstock; Training system